Engineering Cytoplasmic Signaling of CD28ζ CARs for Improved Therapeutic Functions - Meng, Xianhui; Jing, Ruirui; Qian, Liling; Zhou, Chun; Sun, Jie (Frontiers in Immunology, 2020)
Chimeric antigen receptor modified T cells (CAR-T) have yielded impressive clinical outcomes in treating hematopoietic malignancies. However, relapse has occurred in a substantial number of patients and limited the development of CAR-T therapy. Most underlying reasons can be attributed to poor persistence and rapid exhaustion of CAR-T cell in vivo. Despite multiple strategies developed, how to improve CAR-T persistence or resist exhaustion while maintaining sufficient cytotoxic functions is still a great challenge. Here we discuss engineering cytoplasmic signaling as an important strategy for CAR optimization. This review summarizes recent advances that the anti-tumor function of CAR-T cells can be improved by optimizing the CD3ζ domain or downstream signaling of CD28ζ CAR.